An Examination of the Relationship Between Coaches’ Transformational Leadership and Athletes’ Personal and Group Characteristics in Elite Youth Soccer - Erikstad, Martin K.; Høigaard, Rune; Côté, Jean; Turnnidge, Jennifer; Haugen, Tommy (Frontiers in Psychology, 2021)
There is a growing body of literature highlighting the positive impact of transformational leadership behaviours across contexts, including sport. However, there is a lack of knowledge of this relationship within elite sport settings. Thus, the purpose of the present study was to examine the relationship between elite youth athletes’ perceptions of coaches’ transformational coaching-behaviours and variables that have been linked to transformational leadership in other settings (i.e., group cohesion, motivational climate, self-regulation of learning, and athlete satisfaction). Norwegian elite youth soccer players (N = 753) selected into the national talent development program completed questionnaires to measure the variables of interest. Using structural equation modelling, results revealed a positive path from transformational leadership to both task and social cohesion, task-oriented motivational climates, self-regulation of learning, and athlete satisfaction. Finally, a negative path from transformational leadership to ego-oriented climates was identified. The findings are in line with previous research in associating transformational leadership behaviours with adaptive outcomes, and further indicating that such relationships may also be valid in elite sport contexts.